Morphology and elemental analysis of freshly emitted particles from packed-bed domestic coal combustion - Masekameni, Masilu Daniel; Makonese, Tafadzwa; Rampedi, Tebogo Isaac; Keretetse, Goitsemang Salvation (Clean Air Journal, 2020)
This study was conducted in a laboratory-controlled environment to analyse the physical properties and elemental composition of coal combustion particles in a brazier. Particles were sampled 1 m above the stove, using a partector. Particles were collected on gold transmission electron microscopy (TEM) grids, and polycarbonate filters for TEM and inductively coupled plasma mass spectrometry (ICP-MS) analysis, respectively. Particles for elemental analysis were collected on a 37 µm polycarbonate filter, and the exhaust was drawn in using a GilAir Plus pump. During sampling, a 2.5 µm cyclone was attached to the sampling cassette to isolate larger particles. Combustion particles emitted during the early stage of combustion were single organic spherical particles with similar characteristics to tarballs. As the combustion progressed, the particle diameter gradually decreased (from 109 nm), and the morphology changed to smaller particles (to 34.3 nm). The particles formed accretion chain structures, showing evidence of agglomeration. Furthermore, a fluffy microstructure, resembling the formation of soot, was formed in the post flaming phase. In the char-burning phase, an irregular structure of semi-spherical particles was formed, showing evidence of mineral particles infused with small carbonaceous particles. Similarly, with the findings of previous studies, the present research also observed organic spherical particles similar to tarballs. Given that during the ignition phase there was a simultaneous burning of wood as kindling and coal, the provenance of these particle emissions can be attributed to both coal and wood.